Consultations across Languages. Issue 3 (May 2015) - Bibler, Trevor; Peña, Adam; Bruce, Courtenay R.
Abstract Lei, a twenty‐seven‐year‐old Mandarin speaker, visits the United States seeking curative treatments for his acute myeloid leukemia. His mother, Hua, has traveled with him. Neither she nor Lei speak English, and the hospital does not have an onsite professional Mandarin‐speaking interpreter. Using a professional interpreter over the phone, Lei's oncologist, Dr. Branson, attempts to initiate a face‐to‐face goals‐of‐care conversation with Hua as the surrogate decision‐maker. Dr. Branson explains that Lei has "only weeks to months to live" and recommends initiating comfort‐care‐only measures, but Hua says that she wants (and that Lei would want) continued aggressive measures. Hua says that her son might be a candidate for a phase I trial. Eventually, Dr. Branson brings in Dr. Chou, a Mandarin‐speaking resident to provide face‐to‐face interpretation. Hua insists that "there must be more standard therapies available" and says that she will wait until the trial begins. She begins crying, and the meeting disintegrates. Following this, Dr. Branson calls for an ethics consultation for "help in end‐of‐life communicating and reconciling discordance about prognostic information." How should the ethicist use the institution's interpreter services?